Investigation of the phase equilibria in Ti-Ni-Hf system using diffusion triples and equilibrated alloys. (September 2017) - Liu, J.L.; Zhu, L.L.; Huang, X.M.; Cai, G.M.; Jin, Z.P.
Abstract: In present work, the phase equilibrium relations in the Ti-Ni-Hf ternary system, which are of great importance for the design of Ti-Ni based high temperature shape memory alloys, were investigated using diffusion triples and sixteen key equilibrated alloys. Based on the experimental results from electron-probe microscopy analysis (EPMA) and X-ray diffraction (XRD) techniques, two isothermal sections were constructed, which consist of 13 and 12 three-phase regions at 900 °C and 800 °C, respectively. Hf can substitute for Ti in TiNi and Ti2 Ni phases increasing from 30, 62 at% at 800 °C to 36, 64 at% at 900 °C, respectively. The Hf7 Ni10 and Hf9 Ni11 phases show wide ternary composition ranges, while the solubility of Ti in HfNi5, Hf2 Ni7, and HfNi phases are relatively limited. A new ternary phase of τ was detected for the first time, and the stoichiometry of τ phase is close to Ni:(Hf, Ti) = 11:14, with Ti substituting for Hf from ～5 at% to ～22 at%. The single-phase region of the τ phase became narrow as the decreasing of annealing temperature. Based on comparison of phase relations at 900 °C and 800 °C, it is speculated there is an invariant reaction TiNi + τ → HfNi + Ti2 Ni at between 900 °C and 800 °C. Graphical abstract: Highlights: The Ti-Ni-Hf ternary system were systematically investigated using diffusion triples and several key equilibrated alloys. Isothermal sections were determined at 900 °C and 800 °C for the first time. Solid solubility of binary intermetallic compounds were confirmed in Ti-Ni-Hf system. The new ternary phase τ forms through a peritectoid reaction HfNi + Ti2 Hf → τ.